Improvement in performance of N3 sensitized DSSCs with structurally simple aniline based organic co-sensitizers. (1st November 2018) - Naik, Praveen; Abdellah, Islam M.; Abdel-Shakour, M.; Su, Rui; Keremane, Kavya S.; El-Shafei, Ahmed; Vasudeva Adhikari, Airody
Graphical abstract: Structurally simple aniline based D-A type dyes, A1-4 were employed as co-sensitizers at different concentrations in DSSCs sensitized with Ru-II based (N3 ) dye. The results revealed that, theN3 sensitized devices fabricated using co-sensitizer, A2 displayed improved photovoltaic performance in all concentrations, along with CDCA. Highlights: Simple aniline based dyes, A1-4 were employed with N3 dye for co-sensitizing DSSC. Photovoltaic performances were evaluated at different concentrations of dyes. Co-sensitizerA2 carrying N, N -dimethyl barbituric acid outperformed than that ofN3. Device with 0.3 mM ofA2 and 0.2 mM ofN3 displayed the highest PCE of 7.02%. Abstract: In this work, we report comprehensive photovoltaic investigation of four structurally simple D-A configured organic dyes, A1-4 as active co-sensitizers in DSSCs sensitized with well-known Ru (II) basedN3 dye. These effective co-sensitizers (A1-4 ) comprise N, N -dimethylaniline ring as donor scaffold linked with electron withdrawing functionalities, viz . barbituric acid (A1 ), N, N -dimethyl barbituric acid (A2 ), thiobarbituric acid (A3 ), and N, N -diethyl thiobarbituric acid (A4 ) as acceptor/anchoring units. In the present study, for the first time we have demonstrated the profound role of various simple organic molecules carrying different heterocyclic anchoring units on the photovoltaic parameters of theN3 sensitized devices. Also, the effect of concentration of sensitizer/co-sensitizers on the device performance characteristics has been investigated in depth. From the results, it is evident that, the device fabricated using co-sensitizerA2 carrying N, N -dimethyl barbituric acid along with sensitizerN3 in all concentrations outperformed when compared toN3 alone or other co-sensitizers. Interestingly, the best photovoltaic performance was obtained for the co-sensitized device fabricated using 0.3 mM co-sensitizerA2 along with 0.2 mM ofN3 sensitizer. It displayed PCE of 7.02% with JSC of 15.27 mA·cm −2, VOC of 0.671 V and FF of 68.47%. Thus, the observed results have thrown new light upon the device optimization to yield DSSCs with improved performance by the selection of matchable co-sensitizers at appropriate concentrations.